COVID-19 in Cancer Patients, Risk Factors for Disease and Adverse Outcome, a Population-Based Study From Norway - Johannesen, Tom Børge; Smeland, Sigbjørn; Aaserud, Stein; Buanes, Eirik Alnes; Skog, Anna; Ursin, Giske; Helland, Åslaug (Frontiers in Oncology, 2021)
Background WHO has identified cancer as a risk factor for severe outcome of SARS-CoV-2 infection. In this population-based study we aimed to identify factors associated with higher risk of COVID-19 and adverse outcome. Methods Data on all confirmed SARS-CoV-2 positive patients in the period January 1 to May 31, 2020 were extracted from the Norwegian Surveillance System for Communicable Diseases. Data on cancer and treatment was available from the Cancer Registry of Norway, the Norwegian Patient Registry and the Norwegian Prescription Database. Deaths due to COVID-19 were extracted from the Cause of Death Registry. From the Norwegian Intensive Care and Pandemic Registry we retrieved data on admittance to hospital and intensive care. We determined rates of COVID-19 disease in cancer patients and the rest of the population. We also ran multivariate analyses adjusting for age and gender. Results A total of 8 410 patients were diagnosed with SARS-CoV-2 infection in Norway during the study period, of which 547 (6.5%) were cancer patients. Overall, we found similar age adjusted rates of COVID-19 in the population with cancer as in the population without cancer. Unadjusted analysis showed that patients having undergone major surgery within the past 3 months had an increased risk of COVID-19 while we did not find increased Odds Ratio (OR) related to other oncological treatment modalities. No patients treated with stem cell or bone marrow transplant were diagnosed with COVID-19. The fatality rate of COVID-19 among cancer patients was 0.10. This was similar to non-cancer patients, when adjusting for age and sex with OR (95% CI) for death= 0.99, (0.68–1.42). Patients with distant metastases had significantly increased OR of death due to COVID-19 disease of 9.31 (95% CI 2.60–33.34). For the combined outcome death and/or admittance to hospital due to COVID-19, we found significant two-fold increased risk estimates for patients diagnosed with cancer less than one 1 year ago (OR 2.08, 95% CI 1.14–3.80), for those treated with anti-cancer drugs during the past 3 months (OR 1.80, 95% CI 1.07–3.01) and for patients undergoing major surgery during the past 3 months (OR 2.19, 95% CI 1.40–3.44).